Brassinosteroids Regulate OFP1, a DLT Interacting Protein, to Modulate Plant Architecture and Grain Morphology in Rice - Xiao, Yunhua; Liu, Dapu; Zhang, Guoxia; Tong, Hongning; Chu, Chengcai (Frontiers in Plant Science, 2017)
ABSTRACT Brassinosteroids (BRs) regulate important agronomic traits in rice, including plant height, leaf angle, and grain size. However, the underlying mechanisms remain not fully understood. We previously showed that GSK2, the central negative regulator of BR signaling, targets DLT, the GRAS family protein, to regulate BR responses. Here, we identified Ovate Family Protein 1 (OFP1) as a DLT interacting protein. OFP1 was ubiquitously expressed and the protein was localized in both cytoplasm and nucleus. Overexpression of OFP1 led to enlarged leaf angles, reduced plant height, and altered grain shape, largely resembled DLT overexpression plants. Genetic analysis showed that the regulation of plant architecture by OFP1 depends on DLT function. In addition, we found OFP1 was greatly induced by BR treatment, and OsBZR1, the critical transcription factor of BR signaling, was physically associated with the OFP1 promoter. Moreover, we showed that gibberellin synthesis was greatly repressed in OFP1 overexpression plants, suggesting OFP1 participates in the inhibition of plant growth by high BR or elevated BR signaling. Furthermore, we revealed that OFP1 directly interacts with GSK2 kinase, and inhibition of the kinase activity significantly promotes OFP1 protein accumulation in plant. Taken together, we identified OFP1 as an additional regulator of BR responses and revealed how BRs promote OFP1 at both transcription and protein levels to modulate plant architecture and grain morphology in rice.